Clinical Performance of Nurse Trainers from Viewpoints of Student Nurses and Nurse Trainers of Azad Islamic University - Rostami; Rahmani; Ghahremanian; Zamanzadeh (Iran University of Medical Sciences, 2010)
Background and Aim: The quality of clinical education as the main part of nursing education depends on many factors, including the performance of clinical nurse instructors . The aim of this study was to determine and compare the viewpoints of nurse trainers and student nurses of Bonab and Marageh Azad Islamic Universities regarding the performance of clinical nurse instructors.   Material and Method: In this descriptive-comparative study, all clinical nurse instructors (N= 34) and student nurses (N= 200) of two universities were recruited by census sampling. Inclusion criteria for trainers were having Bachelor of Science (BS) degree, having at least one year working experience of clinical teaching, and not participating in clinical teaching in other universities. An inclusion criterion for students was studying in third or fourth year of BS nursing education. For data gathering, a composed questionnaire was used. The first part of the questionnaire consisted of the demographic data of student nurses and nurse trainers . The second part contained 27 items assessing the viewpoints of the subjects regarding clinical performance of clinical nurse instructors in six dimensions including theoretical and skill competency, instruction skills, communication skills, supportive role, directive role and encourage role. Questionnaires were completed by self report method.   Results: Findings showed that both students and trainers believed that the performance of clinical nurse trainers is weak, but, there were statistically significant differences between their views, as students gave lower scores, in all dimensions, than nurse trainers.   Conclusion: These findings demonstrated the weak performance of BS degree clinical nurse instructors in the universities under study. BS degree clinical nurse instructors play an important role in clinical education of student nurses in Azad Islamic Universities, therefore the nursing responsibles of these universities should provide continuing education for clinical nurse instructors.